Economic Efficiency and the Prohibition of Isrāf in Islamic Disaster Relief: A Comparative Cost-Structure Analysis of Flood Response Programs in Aceh Tamiang and Batu Busuak - Slamet Riyadi; Rozaanah Rozaanah (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2026)
This article examines economic efficiency in Islamic disaster relief operations through the lens of the sharīʿah prohibition against isrāf (waste/extravagance) and the maqāṣid principle of ḥifẓ al-māl (preservation of wealth). Drawing empirical evidence from two Indonesian flood response programs—the November 2025 Aceh Tamiang intervention (IDR 138,500,000 serving 270 households) and the December 2025 Batu Busuak response (IDR 57,000,000 serving 150 households)—this study conducts a comparative cost-structure analysis examining resource allocation patterns, logistical efficiency indicators, and operational decisions affecting aid delivery effectiveness. The methodology employs cost-per-beneficiary analysis, procurement strategy assessment, and distribution method evaluation against Islamic public finance principles. Findings reveal that both programs achieved comparable cost-efficiency ratios (IDR 513,000 and IDR 380,000 per household respectively), with divergent strategies for minimizing waste: the Aceh Tamiang program emphasized volunteer mobilization and multi-stakeholder coordination, while the Batu Busuak program leveraged international philanthropy networks and local procurement to reduce transportation costs. Both programs demonstrated alignment with the Islamic prohibition of isrāf through strategic resource allocation, though opportunities exist for enhanced efficiency through standardized procurement protocols and improved logistics coordination. This article contributes to Islamic economic law scholarship by operationalizing classical jurisprudential concepts of waste prohibition within contemporary humanitarian logistics frameworks, proposing sharīʿah-compliant efficiency metrics for disaster relief evaluation.